Effects of Different Treatment Methods of Dried Citrus Peel (Chenpi) on Intestinal Microflora and Short-Chain Fatty Acids in Healthy Mice - Qian, Yujiao; Gao, Zhipeng; Wang, Chen; Ma, Jie; Li, Gaoyang; Fu, Fuhua; Guo, Jiajing; Shan, Yang (Frontiers in Nutrition, 2021)
Chenpi is a kind of dried citrus peel from Citrus reticulata Blanco, it’s often used as traditional Chinese medicine to treat dyspepsia and respiratory tract inflammation. In this study, to determine which way of chenpi treatment play a better effect for the prevention of obesity in healthy mice, we conducted 16S rRNA gene sequencing for intestinal microbiota and GC/MSD analysis for short chain fatty acids (SCFAs) of female rats fed with either chenpi decoction or chenpi powder -based diet (n = 10 per group) for 3 weeks. Chenpi powder group significantly reduced abdominal adipose tissues、 subcutaneous adipose tissue and the serum level of TG. At a deeper level，chenpi powder has a better tendency to increase the ratio of Bacteroidetes to Firmicutes. It alters the Muribaculaceae and Muribaculum in intestinal microbiota，though it is not significant. The concentration of acetic、valeric acid and butyric acids increased slightly but not significantly in chenpi powder group. Chenpi decoction just reduced perirenal adipose tissues, but it shows better antioxidant activity. It has little effect on intestinal microbiota. No differences were found for SCFAs in chenpi decoction group. The results indicated that chenpi powder has better effect in preventing obesity in mice. It can provide a basis for the development of functional products related to chenpi powder.